Ultrasensitive bionic photonic-electronic skin with wide red-shift mechanochromic response - Tianqi Wang; Lei Chen; Haogeng Liu; Haoran Zhu; Zijie Zeng; Yixin Lu; Ping Zhang; Yaofei Chen; Yue Huang; Gui-Shi Liu; Yunhan Luo; Zhe Chen (Light: Advanced Manufacturing)
Mimicking animal skin is an effective strategy for enhancing the performance of artificial skin. Inspired by a chameleon’s iridophore and a spider’s slit organ, a novel photonic-electronic skin (PE-skin) with excellent optical/electrical dual-sensing performance was developed by integrating a photonic crystal (PC) with a conductive MXene/silver nanowire (AgNW) composite into adhesive polydimethylsiloxane. The PC layer containing in-plane-spaced and interplane-packed nanoparticle arrays was fabricated via a fast, facile, combined method of “Marangoni self-assembly”, “plasma etching”, and “adhesive PDMS transfer”. Notably, the PC exhibited a red-shift mechanochromic response through in-plane stretching, which is the first report of sharing the same mechanochromic behavior as a chameleon iridophore. The underlying MXene layer formed slit-organ-like cracks that provided high sensitivity, whereas the AgNWs maintained their conductivity under large strains. The resultant PE-skin exhibited a high mechanochromic sensitivity (2.57 nm %−1) and a high electrical gauge factor of 2600 in a large strain-sensing range (up to 85%). These advantages have been confirmed in the detection of full-range human motions, such as speech recognition, using a deep neural network algorithm. The red-shift stretchable PC demonstrates a new paradigm for artificial chameleon skins, and the bionic PC crack bilayer structure extends the design concept for visually interactive e-skins.